ASSESSMENT OF THE IMPACT OF FOOD SECURITY ON HUMAN CAPITAL DEVELOPMENT (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article examines the impact of ensuring food security on the development of human capital. The study analyzes the level of food security and its influence on key aspects of human capital such as education, healthcare, and economic efficiency.The research highlights that ensuring food security is a critical factor in enhancing public welfare and developing human capital. The authors also propose recommendations for reducing poverty and promoting social equality through the development of food security policies.This article holds significant theoretical and practical value for researchers studying the relationship between food security and human capital, policymakers, and donor organizations.
Keywords: investment, efficiency, healthcare, food, policy.